Уран в организме животных Адриатического моря - Рисик, Н.С. (Вестник зоологии, 1970)
To elucidate the role of uranium in radioecological processes and its effect (as a-emitter) on the living organisms it is necessary to study the accumulation of this ele ment in organisms under natural conditions. The data obtained permitted determining the coefficients of uranium accumulation and its radioactivity in the organism of some animals in the Adriatic Sea. The concentration factors can be of various magnitude from units and tens in Mytilus galloprovincialis to hundreds in Arbacia sp. In the body of Verongia aerophora the microcongeries of uranium are found in which its concentration is higher by two-three orders than the average contents in the organism. In places of localization of such microcongeries higher doses of radiation can be created.